Novel viral translation strategies. (8th July 2014) - Au, Hilda HT; Jan, Eric
Abstract : Viral genomes are compact and encode a limited number of proteins. Because they do not encode components of the translational machinery, viruses exhibit an absolute dependence on the host ribosome and factors for viral messenger RNA (mRNA) translation. In order to recruit the host ribosome, viruses have evolved unique strategies to either outcompete cellular transcripts that are efficiently translated by the canonical translation pathway or to reroute translation factors and ribosomes to the viral genome. Furthermore, viruses must evade host antiviral responses and escape immune surveillance. This review focuses on some recent major findings that have revealed unconventional strategies that viruses utilize, which include usurping the host translational machinery, modulating canonical translation initiation factors to specifically enhance or repress overall translation for the purpose of viral production, and increasing viral coding capacity. The discovery of these diverse viral strategies has provided insights into additional translational control mechanisms and into the viral host interactions that ensure viral protein synthesis and replication. WIREs RNA 2014, 5:779–801. doi: 10.1002/wrna.1246 This article is categorized under: Translation > Translation Mechanisms Translation > Translation Regulation